Pemetaan Daerah Potensi Rawan Banjir Berbasis Wengis Mengunakan Metode Weighted Overlay di Kecamatan Malaka Barat - Michael Lopez; Franki Yusuf Bisilisin (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
Floods are a natural disaster that often occurs in Malaka Barat District, Malaka Regency, East Nusa Tenggara Province, especially due to the overflow of the Benainai River. Every year, floods cause material losses and disrupt community activities. However, until now there has been no clear mapping of areas that are potentially prone to flooding in the region. This study aims to map potential flood-prone areas based on WebGIS using the Weighted Overlay method in Malaka Barat District. This method combines five main parameters, namely elevation, slope, distance from the Benainai River, soil type, and land use, which are weighted based on their level of influence on flood events. The results of the analysis will be visualized in the form of a digital map classified into three levels of vulnerability: low, medium, and high. The WebGIS system developed will facilitate access to information for the community and stakeholders in flood disaster mitigation efforts. This research is expected to be a tool in spatial planning and decision making to reduce the impact of flooding in the area.